Cecal Resection with Bipolar Sealing Devices in a Rat Model. Issue 1 (2nd January 2020) - Tagkalos, E.; Heimann, A.; Gaiser, T.; Hirsch, D.; Gockel, I.; Lang, H.; Jansen-Winkeln, B.
ABSTRACT: Background : Bipolar sealing devices are routinely used to seal blood vessels. The aim of the study is to evaluate the feasibility and safety of colonic sealing with the use of the bipolar energy devices in rats as model for experimental appendectomy. Methods : Seventy-five male Wistar rats underwent a cecal resection with four different bipolar sealing devices or a linear stapler. The harvesting procedure was performed immediately or at postoperative day (POD) 7. The sealing front bursting pressure (BP) was measured in both groups. At POD7, the resection line was clinically examined and the hydroxyproline (HDP) levels were determined. Hematoxylin and Eosin (H&E) staining was used for histopathological evaluation of the sealing front as well. Results : There was no mortality and no insufficiency. The BPs between the bipolar sealing devices showed no statistical differences. The early phase of the seal (POD 0) provides a low BP with an 30.8% increase until POD 7. The BPs in the stapler group showed significant better values. The hydroxyproline levels did not differ statistically between the groups. Histopathologically, there were more signs of ischemic necrosis in the stapler group than in the sealing devices groups. Conclusion : The resection and sealing of the cecum as an experimental appendectomy model with the use of bipolar energy devices proved feasible and safe in rats. The different energy devices in this study produce comparable results. To justify clinical practice in humans, several studies on the underlying mechanisms of early stage wound healing are needed.